f ( x ) = ( cos − 1 2 x ) 2 + π sin − 1 2 x − ( sin − 1 2 x ) 2 + 1 2 π 2 ( x 2 + 6 x + 8 )
If the range of f ( x ) above is [ a π 2 , b π 2 ] , what is the value of 2 ( a + b ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Exactly!! . I think the name of the problem should be dig the d o m a i n .
nice solution .. +1
400 points problem ??
@Rishabh Cool Hey guys, can you guys help me solve this REALLY REALLY HARD GEOMETRY QUESTION
Let ⎩ ⎨ ⎧ α = sin − 1 2 x β = cos − 1 2 x ⟹ sin α = 2 x ⟹ cos β = 2 x ⟹ x = 2 sin α
⟹ sin α ⟹ α β = cos β = sin ( 2 π − β ) = 2 π − β = 2 π − α
Now consider,
f ( x ) ⟹ f ( x ) = ( cos − 1 2 x ) 2 + π sin − 1 2 x − ( sin − 1 2 x ) 2 + 1 2 π 2 ( x 2 + 6 x + 8 ) = β 2 + π α − α 2 + 1 2 π 2 ( 4 sin 2 α + 1 2 sin α + 8 ) = ( 2 π − α ) 2 + π α − α 2 + 3 π 2 ( sin 2 α + 3 sin α + 2 ) = 4 π 2 − π α + α 2 + π α − α 2 + 3 π 2 ( sin α + 1 ) ( sin α + 2 ) = 4 π 2 + 3 π 2 ( sin α + 1 ) ( sin α + 2 )
We note that f ( x ) is maximum and minimum when sin α is maximum and minimum or sin α = 1 and sin α = − 1 respectively. Therefore,
f m a x ( x ) f m i n ( x ) = 4 π 2 + 3 π 2 ( 1 + 1 ) ( 1 + 2 ) = 4 9 π 2 = 4 π 2 + 3 π 2 ( − 1 + 1 ) ( − 1 + 2 ) = 4 π 2
⟹ 2 ( a + b ) = 2 ( 4 9 + 4 1 ) = 5
@Chew-Seong Cheong Can you help me solve this REALLY REALLY HARD GEOMETRY QUESTION
Problem Loading...
Note Loading...
Set Loading...
Note:- Using definition of inverse functions domain of f(x) is [ − 2 , 2 ] .
Use cos − 1 2 x = 2 π − sin − 1 2 x and then expand using identity ( a − b ) 2 = a 2 − 2 a b + b 2 so that most of the terms would cancel and equation would be reduced to a quadratic in x!! f ( x ) = 4 π 2 + 1 2 π 2 ( x + 3 ) 2 − 1 ( x 2 + 6 x + 8 ) = 6 π 2 + 1 2 π 2 ( x + 3 ) 2
Using calculus we can see ( x + 3 ) 2 is increasing in [ − 2 , 2 ] . Hence:-
b π 2 = f ( x ) max = f ( 2 ) = 6 π 2 + 1 2 2 5 π 2
a π 2 = f ( x ) min = f ( − 2 ) = 6 π 2 + 1 2 π 2
Hence,
2 ( 6 1 + 1 2 2 5 + 6 1 + 1 2 1 ) = 5